Antimicrobial Activity of Different Solutions on Denture Base Materials - Tuncdemir, Ali Riza; Uğur, Ayşe Rüveyda; Özdemir, Bilgen; Kahraman, Kübra T. (Journal of Pediatric Infectious Diseases, 2018)
There are a few chemical solutions used for prosthetic cleaning and they have different antimicrobial effects on denture materials. The aim of this study is to evaluate the efficacy of various chemical solutions used in prosthetic cleaning. For this purpose, 40 specimens of polymethylmethacrylate (PMMA-Meliodent, HeraeusKulzer, Hanau, Germany), which is the most commonly used material in conventional prostheses, and 40 specimens of Deflex (Nuxen SRL, Ayacucho 1053 3-A, Cap. Fed. Buenos Aires, Argentina), which is polyamide-containing semi-flexible acrylic, were molded using a template at the laboratory of Dentistry Faculty. Leveling began with abrasive burs and Stones followed by the sanding with medium and thin discs. Surface preparation was done using wet pumice and felt followed by polishing with gypsum-alcohol and rotary soft brush. The evaluated three solutions are Corega cleaning tablets containing alkaline peroxide, 0.2% chlorhexidine gluconate (CG) and 1% sodium hypochlorite (NaOCl). Distilled water was used as the control group. When both groups of polymers were evaluated in respect to the Candida growth after they were kept in liquid containing NaOCl, Corega, and CG, it was observed that only the acrylics that were kept in Corega revealed Candida growth. It was concluded that Corega could not sufficiently inhibit the growth of Candida albicans which is the one of the most common microorganisms in the oral flora of pediatric and elderly patients. NaOCl and CG can be used safely and effectively for denture cleaning.
Keywords: antimicrobial activity; cleaning; denture; solution